2012
DOI: 10.3892/ijo.2012.1706
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of IGF-1 mRNA isoforms in colorectal carcinoma and normal colon tissue

Abstract: Abstract. The insulin-like growth factor (IGF)-1 gene consists of 6 exons resulting in the expression of 6 variant forms of mRNA (IA, IB, IC, IIA, IIB and IIC) due to an alternative splicing. The mechanisms of IGF-1 gene splicing and the role of local expression manifested by IGF-1 mRNA variants in colorectal carcinoma (CRC) have not been extensively investigated. Therefore, the aim of our study was to analyse the expression of IGF-1 mRNA isoforms [A, B, C, P1 (class I) and P2 (class II)], as well as the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 46 publications
1
38
0
1
Order By: Relevance
“…Whereas in colorectal carcinoma, the local expression levels of total IGF-1 mRNA and all splicing isoforms of IGF-1 mRNA were decreased as compared to normal colon tissues. The results of this study suggest an increased regenerative potential in normal colon tissues which, at least partially, is linked to an elevated expression of total IGF-1 mRNA and its isoform A (8). An important clue to the essential role of the IGF-1R in cellular function was uncovered by Sell and co-workers who reported that IGF-1 signaling is an absolute requirement for viral transformation of cells (13).…”
Section: Igf Axis and Cancermentioning
confidence: 73%
See 1 more Smart Citation
“…Whereas in colorectal carcinoma, the local expression levels of total IGF-1 mRNA and all splicing isoforms of IGF-1 mRNA were decreased as compared to normal colon tissues. The results of this study suggest an increased regenerative potential in normal colon tissues which, at least partially, is linked to an elevated expression of total IGF-1 mRNA and its isoform A (8). An important clue to the essential role of the IGF-1R in cellular function was uncovered by Sell and co-workers who reported that IGF-1 signaling is an absolute requirement for viral transformation of cells (13).…”
Section: Igf Axis and Cancermentioning
confidence: 73%
“…Furthermore, it has been shown in two independent studies that human Eb-peptide cleaved form human pre-pro-IGF1b, which is 77 amino acids long, localized to the nuclei of transfected cells and may have IGF-1 independent mitogenic and bioactive properties (46). Notably, a 10-fold decrease in the IGF-1B transcript level was observed (7), and a downshift of the IGF-1B content in favor of the IGF-1A isoform was reported when non-tumor tissue and colorectal cancer cells were analyzed (8). On the other hand, an increase in IGF-1B and decrease in IGF-1A expression were found in cervical cancer and control cells, respectively (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several target proteins were chosen as selectivity counter-screens, including TNF-alpha, FGF-2, G-CSF, IGF-1, and EPO. Similar to that of VEGF, the expression levels of these proteins are post-transcriptionally regulated, either through a 5’-UTR IRES, 3’-UTR AU-rich elements (AREs), or both [3139]. …”
Section: Resultsmentioning
confidence: 99%
“…A differential expression profile of the IGF-I isoforms have been shown in various conditions or pathologies in humans, such as skeletal muscle damage (31,68), endometriosis (35) or prostate (34), cervical (69) and colorectal cancer (137). The diversity and the patterns of differential expression have been proposed to reflect potential biological activities associated with the E domain peptides (27,52).…”
Section: Igf-i Peptides Actions and Signalingmentioning
confidence: 99%